POTENSI DAN PENINGKATAN KUALITAS NUTRISI BUAH TOMAT (Lycopersicon esculentum) AFKIR SEBAGAI PAKAN TERNAK UNGGAS - Ulvi Fitri Handayani; Maria Endo Mahata; Yose Rizal; Irfan Suliansyah; Wizna Wizna (Jurnal Peternakan, 2018)
One of the important things in determining the quality of livestock products is feed ingredients. The quality of Poultry products will be influenced by the nutrient intake provided. Tomato reject is one of the special ingredients of a feed because it contains high lycopene. Lycopene is well known as an antioxidant, also it can lower cholesterol content. However, lycopene still in the matrix of tomato tissue and trans-form lycopene what difficult to digest and absorb in the body. So, in this paper presents the extent to which the development of research utilization of tomatoes high lycopene as poultry feed. As well as opening more widely how to increase the value of lycopene tomatoes in poultry products.